Capitalisms compared - Mjøset, Lars; Clausen, Tommy H. (Comparative social research ;, 2007)
Over the last decade, political economists and other macro-oriented scholars have increasingly focused on the comparative specificities of distinct capitalist systems. Mostly, these systems are studied as national systems. Such models of capitalism are often studied with reference to various institutional dimensions: financial systems, labour relations, welfare state institutions, corporate governance, economic policy making, etc. This volume brings innovative and synthetic contributions combining as many as these institutional dimensions as possible. The issue contains papers by Robert Boyer, A. Tylecote & F. Visintin, Chris McNally & William Lazonick. It also contains a special section based on a contribution by Michael Shalev, "Limits and alternatives to multiple regression in comparative political economy", which addresses techniques of analysing the variety of political-economic constellations in a methodological way. Shalev's views are critically scrutinized by a number of leading scholars, including Charles Ragin, Ro Rothstein, Gosta Esping-Andersen, Jonas Pontusson and others.